Ongoing automated ground deformation monitoring of Domuyo - Laguna del Maule area (Argentina) using Sentinel-1 MSBAS time series: Methodology description and first observations for the period 2015–2020 - Derauw, Dominique Maurice (2020)
Fil: Derauw, Dominique Maurice. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Laboratorio de Estudio y Seguimiento de Volcanes Activos. Río Negro, Argentina.